Foreign Direct Investments of Italian SMEs in Central and Eastern Europe: Case studies of textile firms experience - Lombardo, Giuseppe (My University, 2007)
The internationalisation of business enterprises has been one of the most remarkable factors in the world economy in the twentieth century. Foreign direct investments (FDIs) can be regarded as the most intensive form of foreign operation. However, FDIs have been mainly analysed under the perspective of large and established multinational companies, while minor attention has been paid to small and medium-sized companies. Italian SMEs during the nineties increased their international operations for different reasons: the domestic demand started to flatten out, Italy became very high cost country, emerging countries were progressively upgrading the quality of their products and competition became more compelling. In this respect, the managerial problem is: how could Italian textile SMEs increase competitiveness in their market and in the global market by investing in Eastern and Central European countries, during the period 1990-2005? In order to provide answers to this problem, three objectives are going to be tackled: 1) how ownership, location and internalisation advantages, along with strategic motives, affect the choice of FDI location strategies of Italian textile SMEs in CEE countries, 2) how ownership, location and internalisation advantages, along with strategic motives, affect the choice of FDI ownership strategies and form of investment of Italian textile SMEs in CEE countries, and 3) what strategic motives have triggered Italian textile SMEs to undertake FDIs in CEE countries. The analysis of these objectives is going to be carried out through the use of the eclectic paradigm and the strategic motives for FDIs, as theoretical framework. Then, data about FDI flows from Italy towards CEE countries is provided and finally a questionnaire was sent to two companies, which have been analysed in embedded single-cases. From the cases, it emerged that the two companies adopted different location and ownership strategies, as well as different forms of investment. Instead the motives had similar roots, yet different features
Keywords: FDI; SME; CEE countries; OLI paradigm and strategic motives